Trilemma, dilemma or 2.5-lemma in the transmission of monetary policy : evidence from a Markov-switching panel data model - Alba, Joseph Dennis (2021)
We examine the spill-over effects of interest rate transmission of United States monetary policy to peripheral countries with various exchange rate regimes and capital control management policies. To do so, we propose a two-state continuous-time hidden Markov-switching panel data model using an empirical framework based on the Taylor rule. We find peripheral countries with flexible exchange rates and free capital mobility respond differently to changes in short-term US interest rates under the two regimes based on interest rate volatility. Under the high volatility regime, peripheral countries respond to decreases but not to increases in short-term US interest rate. Under the low volatility regime, peripheral countries respond more strongly to an increase than a decrease in short-term US interest rate. In addition, peripheral countries under high volatility regimes respond more strongly than countries under low volatility regimes to a decrease in short-term US interest rate. In both volatility regimes, capital controls insulate the peripheral countries from changes in the short-term US interest rate regardless their exchange rate regimes.